Economic and social outcomes of investment on market and food systems in Tajikistan - Khakimov, Parviz; Aragie, Emerta A.; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
Findings of World Bank study (WB, SRAS Project 2021) indicates that lack of sufficient quantity and quality of seeds, seedlings, and planting materials in domestic market is one of the critical issues affecting farmers income and food security. Most donor projects provide direct extension support to farmers on multiplying and adopting seeds and seedlings. The local capacity to generate new varieties and planting materials remains low and over 50 percent of all agricultural inputs are imported. The capacity to test new varieties of crops for their adaptation to soils and climate in the country is also lacking, and in general the regular testing of new varieties, whether domestically developed or imported, is not conducted. Between 2016-2019, the share of public agriculture expenditure on inputs distribution to the farmers (0.04 percent or 0.81 million Tajik Somoni) and development of seeds and seedlings (0.8 percent or 16.64 million Tajik Somoni) were low (Khakimov et al. 2024).